Fluticasone Propionate Suppresses Poly(I:C)-Induced ACE2 in Primary Human Nasal Epithelial Cells - Nakazono, Akira; Nakamaru, Yuji; Ramezanpour, Mahnaz; Kondo, Takeshi; Watanabe, Masashi; Hatakeyama, Shigetsugu; Kimura, Shogo; Honma, Aya; Wormald, P. J.; Vreugde, Sarah; Suzuki, Masanobu; Homma, Akihiro (Frontiers in Cellular and Infection Microbiology, 2021)
Background: From its first detection in 2019, SARS-CoV-2 infection has rapidly spread worldwide and has been proven to cause an urgent and important health problem. SARS-CoV-2 cell entry depends on two proteins present on the surface of host cells, angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2). The nasal cavity is thought to be one of the initial sites of infection and a possible reservoir for dissemination within and between individuals. However, it is not known how the genes’ expressions are regulated in nasal mucosa. Objective: In this study, we examined whether ACE2 and TMPRSS2 expressions are affected by innate immune signals in nasal mucosa. We also investigated how fluticasone propionate (FP), a corticosteroid used as the intranasal steroid spray, affects the genes’ expression. Methods: Primary human nasal epithelial cells (HNECs) were collected from the nasal mucosa and incubated with Toll-like receptor (TLR) agonists and/or fluticasone propionate (FP), followed by quantitative PCR, immunofluorescence, and immunoblot analyses. Results: Among TLR agonists, the TLR3 agonist Poly(I:C) significantly increased ACE2 and TMPRSS2 mRNA expressions in HNECs (ACE2 36.212+-11.600-fold change, p<0.0001, and TMPRSS2 5.598+-2.434-fold change, p=0.031). ACE2 protein level was also increased with Poly(I:C) stimulation (2.884+-0.505-fold change, p=0.003). The Poly(I:C)-induced ACE2 expression was suppressed by co-incubation with FP (0.405+-0.312-fold change, p=0.044). Conclusion: The activation of innate immune signals via TLR3 promotes SARS-CoV2 cell entry gene expressions in nasal mucosa and is suppressed in the presence of FP. Further studies are required to evaluate whether FP suppresses SARS-CoV-2 viral cell entry.